KARAKTERISTIK GIZI ABON JANTUNG PISANG (Musa paradisiaca) DENGAN PENAMBAHAN IKAN LAYANG (Decapterus sp). [Nutritional Characteristics Abon of Banana Inflorescence ( Musa Paradisiaca )With Addition Of Scad Fish ( Decapterus sp)] - Mamuaja, Christine F.; Aida, Yuannita (Pascasarjana Unsrat, 2014)
Basically, banana inflorescence is a part of banana trees that useless. Despite it's cheap price the banana inflorescence have benefits as a healthier food ingredients due to the high fiber and low fat content but needed to improve it's protein content by adding high protein food ingredient. The purpose of this study is to know nutritional content of abon which most likeable by the panelist. The research method using completely randomized design (CRD) method consists of 3 treatments (the concentration comparison between banana and fish) with 3 repetitions. The organoleptic test showed that the comparison mixing of banana inflorescence and scad fish based on 4 parameters (taste, texture, color and odor), A2 formula have the highest preference from the panelist. For nutritional content based on proximate analysis treatment (A2) content water = 5.395%, ash = 4,982%, fat=54.169%, protein=19.54% and crude fiber =17.81%.